MENUMBUHKAN JIWA KEWIRAUSAHAAN MELALUI IMPLEMENTASI EDUPRENEURSHIP DI SMK TECHNO MEDIA - Sutihat, Aat; Budiantini, Alya; Jelanti, Desi (Jurnal Abdi Citra, 2024)
The entrepreneurial spirit is a person's willingness to seize business opportunities and create goods or services that add value. With the labor supply not being absorbed by secondary level education graduates at 8.41% for 2023 and the entrepreneurship rate in Indonesia which is still low, with an entrepreneurship ratio of 3.47%. So, this community service aims to foster an entrepreneurial spirit for high school students with the will and creativity to become successful young entrepreneurs and be able to create jobs for people around them. The method developed in this activity is to provide socialization and counseling regarding the EntrepreneurialSpirit accompanied by a pre-test and post-test. So that the existence of activities about fostering an entrepreneurial spirit for students can provide insight, knowledge and skills for students at Techno Media Vocational School.